First detection of a pathogenic avian influenza A/H5N1 clade 2.3.4.4b virus from laying hens in Northwestern Gabon - Gael Darren Maganga; Sonia Etenna Lekana-Douki; Lucie Marquet; Natacha Efoua Tomo; Daniel Obame Ondo; Jumafra Perside Koumba; Landry Mbou Mbina; Michel Dikongo; Barthélémy Ngoubangoye; Jean-Bernard Lekana-Douki; Augustin Mouinga-Ondeme (Cogent Food & Agriculture)
We report the first outbreak of a pathogenic avian influenza virus that occurred on 13 April 2022 in the locality of Meyang, in Gabon, causing the death of 17,498 laying hens. Molecular analysis revealed that the mass mortalities observed in laying hens were associated with serotype H5N1 whose strain belonged to clade 2.3.4.4b. The gabonese Influenza A/H5N1 strains identified showed 99% nucleotide similarity with the Nigerian, Benin and Lesotho strains. The presence of this virus could seriously compromise the development of poultry farming in this country and could threaten public health.